A comparative study between a number of biomechanical variables of the force and throwing positions at the main stage of the backslide and rotation shut pot throwing methods (Damu Journal of Sport Sciences, 2025)
- The differences between the average values ​​of a number of biomechanical variables for the strength and throwing positions at the main stage in the two methods of throwing the shut pot backward slide and rotation for the sample.The researcher used the descriptive approach with the comparison method to suit the objectives and nature of the research. The researcher chose an elite group of the best throwers for the Nineveh Governorate team for the sports season (2022-2023) in the shut pot throwing activity. In the restricted intentional method, who are proficient in throwing the shut pot in both methods, backward slide and rotation, and its structure was (4) throwers as a sample for the research , The sample was homogenized using a coefficient of variation of 30% in the statistical parameters under study . The researcher gave the research sample (throwers) (3) attempts according to the regulations of the international law of the event after they had sufficient warm-up for each throwing method separately for the gliding method and the rotation method. The best attempt in terms of technique and achievement (throwing distance) was chosen for both methods and subjected to kinetic analysis using the (AutoCAD2009) program for the purpose of arriving at the values ​​of the biomechanical research variables under study The researcher concluded :- The shorter the transition time between the two positions (force and throw positions) at the main stage of throwing the shut pot, the higher the speed of performance until reaching the throwing and throwing stage for both methods according to the research results and in favor of the rotation method.- The rotation method by throwing the shut pot showed a greater linear momentum (amount of motion) of the body than the backward sliding method due to the direct relationship between speed and mass.